Does pretraining napping improve time-motion metrics and psychophysiological responses during small-sided games in Ramadan-fasted professional soccer players? - Kerkeni, Mohamed; Ammar, Achraf; Boukhris, Omar; Hbaieb, Eya; Kerkeni, Manel; Zmijewski, Piotr; Chtourou, Hamdi; Aziz, Abdul Rashid; Jahrami, Haitham; Turki, Mouna; Trabelsi, Khaled (Journal of Sports Sciences, 2026)
We examined the effects of a 90-minute nap (N90) during Ramadan fasting (RF) on time-motion and psychophysiological responses during small-sided soccer games (SSGs). Eighteen male professional soccer players (mean ± SD; age: 21.9 ± 1.5 y; estimated VO2max: 55.1 ± 3.2 mL·kg–1 ·min–1) completed four counterbalanced SSGs sessions under N90 and no nap (N0) conditions, one week before and during the third week of RF. Nap duration was monitored via a wrist sleep tracker. Daytime sleepiness was assessed before and after napping. Mood states and hydration status were evaluated before each trial. Time-motion and exercise heart rate (HR) during SSGs were recorded. Blood lactate ([La]) and perceived exertion (RPE) were collected post-sessions. Urine osmolality during RF remained unchanged. The N90 during RF was associated with lower sleepiness (p < 0.001), greater total distance (p = 0.011), and higher running distances at low and moderate-intensity running (p = 0.005 and p = 0.016, respectively). N90 also resulted in lower resting HR (p = 0.021), mean HR (p = 0.006), and relative exercise HR (p = 0.010). N90 was linked to greater vigour (p < 0.001), lower fatigue (p = 0.034), and reduced RPE (p = 0.010). Post-exercise [La] did not differ during RF trials. Pre-SSGs napping may improve time-motion metrics, reduce physiological strain, lower perceived exertion, and enhance mood in Ramadan-fasted professional soccer players.